Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
Management of CNS Tumors 2011
DOI: 10.5772/21100
|View full text |Cite
|
Sign up to set email alerts
|

Brain Tumor and Seizures: Incidence, Pathophysiology, Diagnosis and Treatment

Abstract: xanthoastrocytoma, dysembryoplastic neuroectodermal tumors, and oligodendroglioma are also tumors frequently associated with chronic epilepsy. Overall, it seems likely that low grade, well-differentiated gliomas have higher incidence of seizures than more aggressive glioblastomas or anaplastic astrocytomas (Beaumont 2000; van Breemen, Wilms et al. 2007). The location of the brain tumor also plays a role in the incidence of seizures, because different brain areas are characterized by varying susceptibility to s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 65 publications
0
3
0
Order By: Relevance
“…3 This may not be surprising when considering that peritumoral cortical irritation and the disruption of inhibitory cellular networks are thought to contribute to elevated seizure risk in glioma patients. 19,45,46 Incomplete seizure risk elimination would be expected to accompany the incomplete removal of the offending neoplasm.…”
Section: Seizures and Health Care Quality Accountabilitymentioning
confidence: 99%
“…3 This may not be surprising when considering that peritumoral cortical irritation and the disruption of inhibitory cellular networks are thought to contribute to elevated seizure risk in glioma patients. 19,45,46 Incomplete seizure risk elimination would be expected to accompany the incomplete removal of the offending neoplasm.…”
Section: Seizures and Health Care Quality Accountabilitymentioning
confidence: 99%
“…The incidence rates of seizures in meningiomas, especially in atypical and malignant subtypes, remain understudied [10]. Despite the abundance of knowledge regarding surgical management of resistant forms of epilepsy, including those associated with brain tumors, especially of the low-grade type, prospective studies regarding the medical treatment of epilepsy in this type of patient are scarce [11]. Reportedly, resection of the epileptogenic zone due to the development of brain tumors lead to freedom from or significant control of seizures in 70-90% of patients [12,13].…”
Section: Introductionmentioning
confidence: 99%
“…[18] Treatment of tumor related epilepsy is a complex theme, however recent studies indicated that surgical management supersede medical management. [19] Reportedly, resection of the epileptogenic zone may lead to freedom from or signi cant control of seizures in 70-90% of patients. [20,21] Furthermore, tumor type, seizure severity, early surgical intervention, frequency during the preoperative stage, histopathology of the tumors, and the extension of surgical resection to include peritumoral tissues are, reportedly, the factors that increase the likelihood of freedom from seizures postoperatively.…”
Section: Introductionmentioning
confidence: 99%